HIGHER EDUCATION IN THE USA AND UKRAINE: THE SYSTEMS' DIFFERENCES - O.M. Zarva (Academy of Cognitive and Natural Sciences, 2009)
The article is devoted to the analysis of the Ukrainian and American higher education and to the determination of their differences.